Experiências inclusivas na educação de jovens e adultos em um município do interior paulista - Lima, Fabiana de Oliveira [UNESP] (2015)
The Education for All movements and the struggle for equality of opportunity, equity and universality are contributing to the growing demand for the inclusion of people with disabilities in regular schools. This process has been repeated in all types of education, including the Youth and Adult Education. These young people and adults with disabilities seeking an insert not only in regular schools, but also in the formal labor market. Against this background, the present study aimed to characterize the profile Youth and Adult Education of the student in a city in the interior, between the years 2011 and 2013 and describe the pedagogical practices developed with students with disabilities enrolled in Education Youth and Adults in the interior of São Paulo. The study adopted a qualitative approach and data collection were used; 1) a roadmap to characterize the students, filled from the data collected in the student registration system; 2) a roadmap to characterize the teachers, completed by research participants who were teachers of the Youth and Adult Education First segment that had young students and adults with disabilities in their classes; 3) semi-structured interviews with the same teachers participating in the study. The data collected were organized, analyzed and presented in tables. The interviews were transcribed and the data examined by means of thematic analysis. The results show that the search for Youth and Adult Education was predominantly of women and the elderly. The number of students with disabilities is increasing and when analyzing only this portion of students, however, it is observed that the opposite occurs, with the greatest demand is for males and young people. It was also found that the majority of students with disabilities presents Intellectual Disabilities. Faced with the challenges presented to them, teachers are looking for specific training, updating itself and specializing, which has been reflected in...